POTENSI DAUN TEH HIJAU (Camellia sinensis) SEBAGAI INHIBITOR MAIN PROTEASE (Mpro) COVID-19: SEBUAH STUDI MOLECULAR DOCKINGPOTENSI DAUN TEH HIJAU (Camellia sinensis) SEBAGAI INHIBITOR MAIN PROTEASE (Mpro) COVID-19: SEBUAH STUDI MOLECULAR DOCKING - Haidar Ali Hamzah; Junoretta Haviva Ernanto; Putri Mahirah Afladhanti; Theodorus Theodorus (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
COVID-19 caused by SARS-CoV-2 has been a challenge for researchers accross the world to find effective drugs of the disease. This study aims to know the potential compounds of tea leaves (Camellia sinensis) as a COVID-19 Mpro inhibitor using molecular docking study. This study used 12 compounds in tea leaves and lopinavir as a comparison. Lipinski analysis was carried out to assess potential compounds as a drug. Docking was carried out by AutodockTools 1.5.6 and Autodock Vina. The visualization were carried out by Discovery Studio v16. The results showed that all compounds compiled the criteria as a drug based on Lipinski rules. Catechin and epicatechin have the same energy bond as lopinavir which is -7,1 kcal/mol, while catechin gallate, epicatechin gallate, kaempferol, quercetin, and myricetin are proven to have the strongest binding energy compared to lopinavir which is -9,0, -8,2, -,7,8, -7,5, and -7,4 kcal/mol. All compounds bind at the active site of the Mpro COVID-19 so they are characterized as competitive inhibitor with amino acid residues such as Cys145, His41, and Glu166. Based on the results, catechin gallate, epicatechin gallate, catechin, epicatechin, kaempferol, quercetin, and myricetin have the potential to be competitive inhibitors of COVID-19 Mpro.